2003
DOI: 10.1007/s11663-003-0004-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase-equilibrium data and liquidus for the system “MnO”-CaO-Al2O3-SiO2 at Al2O3/SiO2 of 0.55 and 0.65

Abstract: Phase-equilibrium data and liquidus isotherms for the system "MnO"-CaO-(Al 2 O 3 ϩ SiO 2 ) at silicomanganese alloy saturation have been determined in the temperature range of 1373 to 1723 K. The results are presented in the form of the pseudoternary sections "MnO"-CaO-(Al 2 O 3 ϩ SiO 2 ) with Al 2 O 3 /SiO 2 weight ratios of 0.55 and 0.65. The primary-phase fields have been identified in this range of conditions. and, subsequently, mounted and polished for further examination. On quenching, the liquid phase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 3 publications
3
19
0
Order By: Relevance
“…Roghani et al 26,27) reported compositions of gehlenite in equilibrium with the liquid which deviate significantly from the stoichiometric composition, whereas in the present study the measured compositions were much closer to stoichiometric Ca 2 SiAl 2 O 7 , as shown in Fig. 7.…”
Section: Phase Diagrams Of Thesupporting
confidence: 64%
See 4 more Smart Citations
“…Roghani et al 26,27) reported compositions of gehlenite in equilibrium with the liquid which deviate significantly from the stoichiometric composition, whereas in the present study the measured compositions were much closer to stoichiometric Ca 2 SiAl 2 O 7 , as shown in Fig. 7.…”
Section: Phase Diagrams Of Thesupporting
confidence: 64%
“…However, these results are quite scattered and in disagreement with each other and with experimental data shown in Fig. 4 26,27) reported phase equilibrium studies at Al 2 O 3 /SiO 2 weight ratios of 0.41, 0.55 and 0.65 at temperatures between 1 100°C and 1 450°C. As well, there are the results of the present experiments (Table 1).…”
mentioning
confidence: 53%
See 3 more Smart Citations